JARANAN MATARAMAN ART: REPRESENTATION OF HISTORY AND MORAL VALUES IN DUSUN SANAN, BLITAR - Fitriyah, Aidatul; Baskoro, Ilham; Firnanda, Retno Asih; Hamdan, Ahmad (ISLLAC : Journal of Intensive Studies on Language, Literature, Art, and Culture, 2024)
This study aimed to examine the history and moral values of Jaranan Mataraman Art as a cultural identity of residents of Sanan Blitar Hamlet. This research used a qualitative method with a case study approach. Data collection was done through observation and interviews. Research data were obtained from observing Jaranan Mataraman's performances in Sanan Hamlet, Dayu Village, and Blitar Regency. Researchers also interviewed Jaranan Mataraman art activists in Sanan Hamlet using an open-ended questionnaire system. The results of this study revealed that every movement of Jaranan Mataraman's art consists of historical and moral values. There is a correlation between animist aspects such as danyang and the importance of maintaining the Sumber Sanan water source for residents. Therefore, Jaranan Mataraman was designated as the cultural identity of the people of Sanan Hamlet and became an intangible cultural heritage. From this research, it can be concluded that the art of Jaranan Mataram represents the dynamics of local history and moral values so that it can be established as a cultural identity in the Sanan Hamlet community and formalised as an intangible cultural heritage.